Somatic and neurobiologic development of mice exposed to variable offer of omega 3 fatty acids during perinatal life - Bianconi, Santiago (2013)
Fil: Bianconi, Santiago. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Cátedra de Fisiología Humana; Argentina